2004
DOI: 10.1063/1.1828605
|View full text |Cite
|
Sign up to set email alerts
|

Observation of dislocations in diffused 4H–SiC p-i-n diodes by electron-beam induced current

Abstract: The electron-beam induced current (EBIC) method was employed to investigate the electrical activity of dislocations in silicon-carbide-diffused p-n diodes. It was observed that EBIC contrast depends on the type of defect (superscrew, screw, and edge dislocation). This dependence was attributed to spatial inhomogeneities in the electrical properties of the material around the dislocations due to different impurity-dislocation interactions during high-temperature (∼1900°C) diffusion. Chemical etching of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…With increasing reverse bias voltage, intensity of the bright spots monotonically increased and spots eventually changed into higher intensity around 4.5 V. It is considered that generated carriers by irradiated EB are transported via defect sites, same as the mechanism of the leakage current conduction. Similar behavior has been reported in diamond Schottky barrier diodes, SiC PIN diodes, and Si‐metal‐oxide‐semiconductor (MOS) structure …”
Section: Resultssupporting
confidence: 76%
“…With increasing reverse bias voltage, intensity of the bright spots monotonically increased and spots eventually changed into higher intensity around 4.5 V. It is considered that generated carriers by irradiated EB are transported via defect sites, same as the mechanism of the leakage current conduction. Similar behavior has been reported in diamond Schottky barrier diodes, SiC PIN diodes, and Si‐metal‐oxide‐semiconductor (MOS) structure …”
Section: Resultssupporting
confidence: 76%
“…The spots observed via OBIC are similar to those detected via electron beam induced current ͑EBIC͒ by Maximenko et al 11 There, these spots were identified through KOH etching as converted edge dislocations. As indicated previously, partial dislocations associated with Shockley stacking faults that are predominant in SiC pin diodes appear as broad dark areas of suppressed current ͓Fig.…”
Section: B Dislocationssupporting
confidence: 79%
“…Further studies involving KOH etching and EBIC imaging, similar to the work by Maximenko et al, 11 would aid in furthering the ability of OBIC in identification and separation of screw and edge dislocations. Furthermore, by utilizing a method similar to that used in the EBIC measurements, 20-22 the ambipolar carrier diffusion lengths may be estimated.…”
Section: Discussionmentioning
confidence: 87%
“…EBIC has been used to measure minority carrier diffusion length in both 4H-and 6H-SiC [91,92]. It also has been used to characterize electrical active surface defect in 4H-SiC diodes [93,94].…”
Section: Pulsed Mos Capacitor (C-t)mentioning
confidence: 99%